Dynamic capabilities in international markets: their antecedents and current and future performance outcomes - Lisboa, Ana Catarina Cadima (2012)
The international context is a dynamic, complex environment in which it is hard for firms to secure current performance without hindering future performance. This study developed specific dynamic capabilities as a feasible way to balance current and future export performance. Besides including an important domain to dynamic capabilities (market) and considering the relevant but understudied context of exporting, the study’s contribution is threefold: (1) it extends previous work and studies the impact of export market orientation on product development and market-related dynamic capabilities, (2) it is the first to disentangle the effects of dynamic capabilities on current and future performance, and (3) it tests interfunctional coordination and environmental turbulence as moderators of the dynamic capabilities–performance link. An online survey was administered to Portuguese export manufacturers. The findings suggest that export market orientation dimensions – customer and competitor – are not similarly related to dynamic capabilities. Export customer orientation is an antecedent of both exploitative and explorative capabilities, whereas export competitor orientation promotes only exploitative capabilities. The effects of dynamic capabilities on current and future performance are distinct. Exploitative capabilities are positively related to current performance. Product development explorative capabilities are positively related to current performance, whereas market-related explorative capabilities have the opposite effect. Market-related exploitative capabilities and product development explorative capabilities relate positively to future performance. With respect to moderating effects, findings confirm the role of interfunctional coordination as moderator of the explorative capabilities– performance link. Environmental turbulence dimensions – technological and market – moderate the dynamic capabilities–performance link, but do so divergently.